A comparative study of cell block and cytological smears in FNAC of intra-abdominal lesions - Anita A M; MD Hamed Altaf Mali; Anuradha G Patil; Meenakshi M (Journal of Pathology of Nepal)
Background: Cell blocks are micro biopsies and are complimentary to cytology smears and give a = more accurate diagnosis. This study aimed to study cell block as an adjunct for FNAC smears in intra- abdominal lesions, and to compare the sensitivity and specificity of the cell block with FNACs of intra- abdominal lesions.